The conceptualization of change management models at the enterprises in modern changing environment - Гринько, Тетяна Валеріївна; Гвініашвілі, Тетяна Зурабівна (Technology audit and production reserves, 2015)
Nowadays change management occupies an important place in the management of the organization, and the very changes are an integral part of successful business organizations. The development of enterprise as the acquisition of new quantitative and qualitative properties is impossible without an implementation of changes. Thus, the development of entrepreneurship is only possible on the basis of effective change management in the company, owning significant theoretical principles of change management, analysis of the main factors, methodological aspects and models of change management in enterprises in a changing environment. Analysis of patterns of change management allowed to make the conclusion that nowadays there is no single universal model of change management that would ideally correspond to the current economic conditions, characteristics and organizational culture and would certainly guarantee the success of changes. In a result of critical analysis of change management models, based on a particular approach, it should be noted that only the use of an integrated approach to change management can ensure their successful implementation. The proposed algorithm of change management in enterprises allows to achieve positive results of institutionalize changes. Criteria for selection has been set, on which the right choice for a model change management should be based. Revealed possible causes of failure successful change management, amongst it are the resistance to change from the side of employees what will be concentrated and further research at. The obtained results of the study, in particular, the method of selection of the model of change management and application of the proposed algorithm supplement and develop existing knowledge, contribute the performance, stability and sustainability of the enterprise.